APPLICATION OF ORNAMENTAL PLANT SPECIES IN SANGGAR SKILLA USING MICROSOFT VISUAL BASIC 6.0 - Suyanti Suyanti; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2004)
At present there are still many plants that convey a workshop information by manual and time consuming for potential consumers. Therefore in this paper the author tries to answer the problems of this by making an application  to facilitate the consumers get the information in these centers. Applications created by this author introduces an application form Sanggar SKILLA Ornamental Plants of the founding history, a collection of ornamental plants owned by its information by using Microsoft Visual Basic 6.0 applications.